Responding to old problems in the Dutch work addiction scale: a psychometric approach in a Peruvian sample - Salas-Blas, Edwin (2025)
Background: Harmful work patterns have become a public health problem. These conditions are worrying since they can have an impact on mental health, social conflicts, and physical difficulties due to their normalization of pathological behaviors related to work addiction. Aims: (1) determine the psychometric properties and reliability of the DUWAS and (2) evaluate valid comparisons at the construct level. Methods: The Spanish version of DUWAS was used. For the evaluation of the psychometric model, 446 Peruvian workers responded to the Spanish version (60.5% women aged 18 to 65, M = 35.1 SD = 12.45). Results: The unidimensional version was confirmed (x2 = 67.495(14); CFI = 0.96; TLI = 0.95; SRMR = 0.050 and RMSEA = 0.069). The reliability was acceptable (α = 0.735; 95% CI: 0.706 − 0.762; ω = 0.741; 95% CI: 0.712 − 0.767) and measurement invariance was confirmed for sex and age groups. Concurrent validity was mostly identified with mental health indicators. Conclusion: This study provides new information on dimensionality and the realization of valid comparisons that allow its use in Spanish-speaking workers.